2019
DOI: 10.1038/s41467-019-12253-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-host interplay in atopic dermatitis and psoriasis

Abstract: Despite recent advances in understanding microbial diversity in skin homeostasis, the relevance of microbial dysbiosis in inflammatory disease is poorly understood. Here we perform a comparative analysis of skin microbial communities coupled to global patterns of cutaneous gene expression in patients with atopic dermatitis or psoriasis. The skin microbiota is analysed by 16S amplicon or whole genome sequencing and the skin transcriptome by microarrays, followed by integration of the data layers. We find that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
243
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(280 citation statements)
references
References 69 publications
11
243
0
4
Order By: Relevance
“…In contrast, the skin microbiome of AD patients was highly over-represented by Staphylococcus (S.) aureus which allowed the discrimination of a S. aureus "low" and "high" colonized state. The latter one was shown to be paralleled by increased barrier dysfunction (e.g., CLDN8, FLG) and a stronger immune cell related profile (e.g., IL13, IL5) [148,151]. This identified "high" colonized state may also be more prone to HSV-1 infections as it is seen in ADEH+ patients [88].…”
Section: Disease Subgroupingmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, the skin microbiome of AD patients was highly over-represented by Staphylococcus (S.) aureus which allowed the discrimination of a S. aureus "low" and "high" colonized state. The latter one was shown to be paralleled by increased barrier dysfunction (e.g., CLDN8, FLG) and a stronger immune cell related profile (e.g., IL13, IL5) [148,151]. This identified "high" colonized state may also be more prone to HSV-1 infections as it is seen in ADEH+ patients [88].…”
Section: Disease Subgroupingmentioning
confidence: 88%
“…As skin is a major body site directed toward environmental impacts, the microbiome is a crucial player in the tissue homeostasis and fine-tuned regulation between immune activation and tolerance is necessary [147]. A recent study revealed the existence of different endotypes according to the microbiome and revealed a high diversity of microbial species in psoriatic skin [148,149]. As dysregulated EDC members often show antimicrobial activity (e.g., S100s and LECs), the investigation of the microbiome in dependency of genetic mutations would be intriguing [150].…”
Section: Disease Subgroupingmentioning
confidence: 99%
“…In terms of cutaneous pathophysiology, shifts in the composition of the cutaneous microbiome (dysbiosis) have been identified in a range of inflammatory and autoimmune conditions including psoriasis [49][50][51][52], atopic eczema [53][54][55], bullous pemphigoid [56,57] and acne vulgaris [58]. Building on the evidence from culture-based studies that HS is associated with dysbiosis, Guet-Revillet et al [59] employed both culture and metagenomic techniques to comprehensively characterise the cutaneous microbiome in HS.…”
Section: The Benefits Of 16s Rrna Sequencing and Metagenomic Approachesmentioning
confidence: 99%
“…Currently, exploration of the skin microbiome in AD is attracting more and more attention from researchers. Dysbiosis in microbiota has been universally considered an important factor in the pathogenesis of AD, and how to achieve and maintain a balance between skin microbiota and the host has become a hot research topic in the field of AD treatment [10]. Although traditional treatments including topical glucocorticoid and calcineurin inhibitors can inhibit inflammation, the recurrence of AD continues.…”
Section: Introductionmentioning
confidence: 99%